Perinatal diagnosis, management, and follow-up of cystic renal diseases: a clinical practice recommendation with systematic literature reviews - Gimpel, Charlotte; Schaefer, Franz (JAMA pediatrics, 2018)
Importance: Prenatal and neonatal cystic kidney diseases are a group of rare disorders manifesting as single, multiple unilateral, or bilateral cysts or with increased echogenicity of the renal cortex without macroscopic cysts. They may be accompanied by grossly enlarged kidneys, renal oligohydramnios, pulmonary hypoplasia, extrarenal abnormalities, and neonatal kidney failure. The prognosis is extremely variable from trivial to very severe or even uniformly fatal, which poses significant challenges to prenatal counseling and management. Objective: To provide a clinical practice recommendation for fetal medicine specialists, obstetricians, neonatologists, pediatric nephrologists, pediatricians, and human geneticists by aggregating current evidence and consensus expert opinion on current management of cystic nephropathies before and after birth. Methods: After 8 systematic literature reviews on clinically relevant questions were prepared (including 90 studies up to mid-2016), recommendations were formulated and formally graded at a consensus meeting that included experts from all relevant specialties. After further discussion, the final version was voted on by all members using the Delphi method. The recommendations were reviewed and endorsed by the working groups on inherited renal disorders of the European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) and European Society for Paediatric Nephrology (ESPN); the German Society of Obstetrics and Gynecology (DGGG), German Society of Perinatal Medicine (DGPM), and German Society of Ultrasound in Medicine (DEGUM); and the alliance of patient organizations, PKD International. Recommendations: The group makes a number of recommendations on prenatal and postnatal imaging by ultrasound and magnetic resonance imaging, genetic testing, prenatal counseling, in utero therapeutic interventions, and postnatal management of prenatal and neonatal cystic kidney diseases, including provision of renal replacement therapy in neonates. In addition to detailed knowledge about possible etiologies and their prognosis, physicians need to be aware of recent improvements and remaining challenges of childhood chronic kidney disease, neonatal renal replacement therapy, and intensive pulmonary care to manage these cases and to empower parents for informed decision making.
Gesehen am 02.05.19